The Influence of Perceived Acculturative Stress on Psychological Stress Response Being Mediated by Coping Strategies Among Japanese Mothers in Thailand - Kurata, Mai; Varma, Parvathy (Scholar: Human Sciences, 2021)
This study attempts to assess the impact of the direct and indirect influence of acculturative stress on the stress response of Japanese mothers in Thailand mediated by the three Coping strategies. A convenient sample of 246 Japanese mothers were given a survey on acculturative stress, problem solving support seeking coping, avoidance thinking coping, positive thinking distraction, and stress response, The indirect relationship between acculturative stress and stress response is supported only when it was mediated by positive thinking-distraction coping strategy. The From the overall findings it can be inferred that the level of stress experienced However, the use of positive thinking-distraction coping strategy when they perceive distress was found to be effective among Japanese mothers. in order to effectively cope with the stress. Further study required for the practical way to encourage Japanese mothers in Thailand to utilize positive thinking-distract coping strategy.